2011 Proceedings IEEE INFOCOM 2011
DOI: 10.1109/infcom.2011.5934915
|View full text |Cite
|
Sign up to set email alerts
|

Geography-based analysis of the Internet infrastructure

Abstract: Abstract-In this paper, we study some geographic aspects of the Internet. We base our analysis on a large set of geolocated IP hop-level session data (including about 300, 000 backbone routers, 130 million end hosts, and one billion sessions) that we synthesized from a variety of different input sources such as US census data, computer usage statistics, Internet market share data, IP geolocation data sets, CAIDA's Skitter data set for backbone connectivity, and BGP routing tables. We use this model to perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…The correlation coefficient between hop count and distance was identified as r = 0.32 with the linear model equal to y [ms] = 0.001576 x [km] + 11.97. Compared to the results presented in [17], the correlation coefficient for the US was about 0.15. This finding means that the hop count is slightly more dependent on the distance in Europe than in the US, but still is too small to make it usable for measurement-based Geolocation.…”
Section: Meancontrasting
confidence: 71%
See 1 more Smart Citation
“…The correlation coefficient between hop count and distance was identified as r = 0.32 with the linear model equal to y [ms] = 0.001576 x [km] + 11.97. Compared to the results presented in [17], the correlation coefficient for the US was about 0.15. This finding means that the hop count is slightly more dependent on the distance in Europe than in the US, but still is too small to make it usable for measurement-based Geolocation.…”
Section: Meancontrasting
confidence: 71%
“…Geographical properties of the Internet are also studied to improve IP Geolocation accuracy. In [17], Kasiviswanathan et al studied the relationship between routing paths and geographical distance. They analysed routing paths in the US using several datasets such as Skitter and ip2location.…”
Section: Related Workmentioning
confidence: 99%
“…Measurements on the Internet concluded that in the United States about 96% of paths have less than 3 hops counted in autonomous systems (i.e. domains) [33]. The number of messages that an NSA exchanges with the domain nodes' for link capacity updates and slice set up are proportional, respectively, to the number of nodes I m and the number of hops on the intra-domain path per session H m k,s .…”
Section: Complexity Of Deens and Signaling Overheadmentioning
confidence: 99%
“…The number of messages that an NSA exchanges with the domain nodes' for link capacity updates and slice set up are proportional, respectively, to the number of nodes I m and the number of hops on the intra-domain path per session H m k,s . The number of hops per session on Internet is measured in [33], [34] and it is found that one session on average has between 5 and 20 hops. Alternatively, we can use the small world approximation [35] for the average number of hops for one session (k, s) is m∈M k,s log(I m ).…”
Section: Complexity Of Deens and Signaling Overheadmentioning
confidence: 99%
“…Kasiviswanathan et al [10] studied the geographical aspects of the Internet. The measurements were focused on the global US and particular US states.…”
Section: Related Workmentioning
confidence: 99%